Deaths due to Gunshot Wounds in City of Aydın - Cingöz, Gökhan; Erel, Özlem; Dirlik, Musa; Özkök, Mustafa Selim; Katkıcı, Ufuk (The Bulletin of Legal Medicine, 2010)
Our aim in this study is to discuss the differences and the causes between the death cases due to gunshot wounds which happened in Aydin and the studies that are done about this same subject in our country and worldwide. In our study gender, age, occupation, crime scene, origin, season, month, year, type of weapons, number of rounds in and out, shooting range, whether there is additional evidence of trauma, cause of death, therapeutic presence, bullet entry side of the autopsies of 146 deaths due to gunshot wounds that were done by our department between 2004 and 2009 were evaluated, all the data obtained was processed to the program SPSS 14.0 for Windows and put into the charts. There were a total of 146 death cases due to gunshot wounds determined. These cases make up 8.8% of all forensic autopsies. 91.8% of the cases were male, and 8.2% were female. In the distribution of age groups 31-40 age group was the highest with the rate of 30.1%.In the distribution of the type of weapon used; it was determined that 58.2% gun, 40.4% hunting rifle and 1.4% war weapons were used. According to the origin of the cases; homicides take the first place with 52.7%, suicides comes next with 37%, following deaths due to accidents with 2.7%, and the origins of 7.5% cases weren’t determined. And in the area of entry lesions on the body; head comes first with 41.8%. As in the world and in different regions of our country, deaths due to gunshot wounds take an important place in forensic autopsy cases in Aydin also. It shows us that more precautions should be taken about the control of gunshots and public awareness.Key words: Gunshot, origin, death, autopsy
Keywords: gunshot; origin; death; autopsy